Resveratrol attenuates oxidative stress and muscle damage in sedentary rats subjected to physical exercise - Narciso, L. G. [UNESP]; Almeida, B. F.M. [UNESP]; Bosco, A. M. [UNESP]; Pereira, P. P. [UNESP]; Vendrame, K. E. [UNESP]; Louzada, M. J.Q. [UNESP]; Ciarlini, P. C. [UNESP] (FapUNIFESP (SciELO), 2018)
Physical inactivity is a public health problem when a sedentary population practices physical activity sporadically. Exercise in unconditioned individuals causes oxidative stress and muscle damage. This study tested the hypothesis that a single physical exertion can cause muscle damage and oxidative stress in sedentary individuals, and resveratrol can attenuate it. For this, 40 sedentary adult male rats were equally and randomized into four groups subjected to 90min swimming or rest and administered aqueous resveratrol (100mg/kg/day) or saline for 14 days: N-RV-, rats maintained at rest and administered saline; N-RV+, rats maintained at rest and treated with resveratrol; N+RV-, rats subjected to physical exercise and administered saline; and N+RV+, rats subjected to physical exercise and treated with resveratrol. In sedentary rats, the physical exertion of swimming promoted oxidative stress, i.e. increased lipid peroxidation and decreased plasma total antioxidant capacity, and significant increases in CK and LDH plasma activities. Resveratrol diminished lipid peroxidation and the concentrations of muscle damage markers (CK and LDH) in sedentary rats subjected to swimming. The results provide evidence that a single sudden physical exertion can cause oxidative stress in sedentary rats. Resveratrol showed good results as a treatment for minimizing muscle damage caused by this stress.
Resveratrol atenua o estresse oxidativo e a lesão muscular de ratos sedentários submetidos ao exercício físico
Keywords: Antioxidant treatment; Oxidative stress; Physical exertion; Physical inactivity